SecA2 associates with translating ribosomes and contributes to the secretion of potent IFN-β inducing RNAs - Teubner, Lisa; Frantz, Renate; La Pietra, Luigi; Hudel, Martina; Bazant, Jasmin; Lochnit, Günter; Eismann, Lena; Kramer, Günter; Chakraborty, Trinad; Abu Mraheil, Mobarak (International journal of molecular sciences, 2022)
Protein secretion plays a central role in modulating interactions of the human pathogen Listeria monocytogenes with its environment. Recently, secretion of RNA has emerged as an important strategy used by the pathogen to manipulate the host cell response to its advantage. In general, the Sec-dependent translocation pathway is a major route for protein secretion in L. monocytogenes, but mechanistic insights into the secretion of RNA by these pathways are lacking. Apart from the classical SecA1 secretion pathway, L. monocytogenes also encodes for a SecA paralogue (SecA2) which targets the export of a specific subset of proteins, some of which are involved in virulence. Here, we demonstrated that SecA2 co-sediments with translating ribosomes and provided evidence that it associates with a subset of secreted small non-coding RNAs (sRNAs) that induce high levels of IFN-β response in host cells. We found that enolase, which is translocated by a SecA2-dependent mechanism, binds to several sRNAs, suggesting a pathway by which sRNAs are targeted to the supernatant of L. monocytogenes.
Gesehen am 07.02.2022